Development of Nanogel Loaded with Lidocaine for Wound-Healing: Illustration of Improved Drug Deposition and Skin Safety Analysis - Amena Ali; Abuzer Ali; Mohammad Akhlaquer Rahman; Musarrat Husain Warsi; Mohammad Yusuf; Prawez Alam (Gels, 2022)
A wound refers to a cut or blow that may result in primary or secondary infection or even death, if untreated. In the current study, we have explored the wound-healing properties of lidocaine nanogel, owing to its antioxidant and neutrophilic modulatory potential. Initially, the pre-formulation study was performed and then using central composite design (CCD) fabrication and the characterization of lidocaine-loaded nanoemulsion was carried out. After the preparation of a nanogel of lidocaine-loaded nanoemulsion, it was evaluated on various parameters, such as pH, spreadability, extrudability, drug content, in vitro drug release, dermatokinetic study and in vivo skin safety. Based on the pre-formulation study, the maximum solubility of lidocaine was found in oleic acid (324.41 ± 4.19 mg/mL) and in Tween 20 (192.05 ± 8.25 mg/mL), selected as a suitable emulsifier. The refractive index of the optimized nanoemulsion was found to be 1.35 ± 0.04, the electrokinetic potential was recorded as −15.47 ± 0.95 mV. The pH, spreadability and extrudability of nanogel was found to be 6.87 ± 0.51, 73.32 ± 4.59 gm.cm/sec and 107.41 ± 6.42 gm/cm2, respectively. The percentage of the cumulative drug content and drug release from nanogel was found to be 99.94 ± 1.70% and 93.00 ± 4.67%, respectively. Moreover, dermatokinetic study showed significantly (p < 0.0005) improved drug deposition and the in vivo skin safety study showed no sign of dermal erythematous lesion or any visible damage. Stability studies also testified the secureness of nanogel after storage in a prescribed environmental condition. Thus, this study provides substantial evidence for healing wounds effectively and the further evaluation of the in vivo model. The patent related to this work was published in the Indian Official Journal of the Patent Office (Issue number: 20/2022).